2019
DOI: 10.1029/2018jd029667
|View full text |Cite
|
Sign up to set email alerts
|

Midlatitude Oceanic Cloud and Precipitation Properties as Sampled by the ARM Eastern North Atlantic Observatory

Abstract: Marine low clouds are critical to the climate system because of their extensive coverage and associated controls on boundary layer dynamics and radiative energy balance. The primary foci for this study are marine low cloud observations over a heavily instrumented site on the Azores archipelago in the Eastern North Atlantic and their associated raindrop size distribution (DSD) properties, relative low cloud contributions to the precipitation, and additional sampling (instrument, environmental) considerations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 67 publications
(115 reference statements)
5
31
0
Order By: Relevance
“…However, when we redid the calculations of Table 2 separately for daytime and nighttime observations at the ENA, the results did not change. The site is situated along the northern coast of the Graciosa Island, which displays some variations in topography with elevations up to 400 m south of the site (e.g., Giangrande et al, 2019). When we removed southerly wind conditions from the ENA data set, the sensitivities of Table 2 did change slightly, enough to suggest that the island has some impact on the observations but not enough to bring sensitivities to surface temperature on par with what is found with the SO data sets.…”
Section: 1029/2020jd032465mentioning
confidence: 99%
“…However, when we redid the calculations of Table 2 separately for daytime and nighttime observations at the ENA, the results did not change. The site is situated along the northern coast of the Graciosa Island, which displays some variations in topography with elevations up to 400 m south of the site (e.g., Giangrande et al, 2019). When we removed southerly wind conditions from the ENA data set, the sensitivities of Table 2 did change slightly, enough to suggest that the island has some impact on the observations but not enough to bring sensitivities to surface temperature on par with what is found with the SO data sets.…”
Section: 1029/2020jd032465mentioning
confidence: 99%
“…In order to ensure quality DSDs, artifacts that are due to splashing or other causes need to be removed. Following Giangrande et al (2019) and Wang et al (2018)'s analysis of VDIS DSDs, thresholds that check drop fall speed and particle diameter were applied to filter out splashing. After that, the DSDs were averaged to 1 minute to reduce noise and then fitted to a normalized gamma distribution of the form…”
Section: Disdrometersmentioning
confidence: 99%
“…determined by two parameters N w and D 0 (Testud et al, 2001). These fits were produced using the method of moments technique in PyDSD (Ulbrich and Atlas, 1998;Hardin and Guy, 2017) utilized in past ARM efforts analyzing VDIS and J-W DSDs (Giangrande et al, 2014a(Giangrande et al, , 2019Wang et al, 2018). In order to ensure a statistically significant sample required to calculate the gamma distribution parameters, only DSDs with greater than 100 drops and rainfall rates greater than 0.5 mm hr −1 were included.…”
Section: Disdrometersmentioning
confidence: 99%
See 1 more Smart Citation
“…Raindrop size distribution (DSD) is the most fundamental microphysical property of precipitation. Extensive literature has revealed that the DSD characteristics vary with rain categories, geographical locations, storm to storm, and season to season [16][17][18][19][20][21][22][23]. Modeled DSD parameters are crucial for satellite-based rainfall estimation algorithms.…”
Section: Introductionmentioning
confidence: 99%